Digital Competency in Teaching: Evaluating Computer-Based Learning in Basic Education - Escalante, Cefrenito; Tilus, Jan Cleo Mar; Oclarit, Jocelyn; Perez, Eugenia; Gultian, Janice; Pagaran, Kris; Dano, Arlene; Neri, Remcil; Mortejo, Reycher (International Journal of Social Sciences and English Literature, 2025)
This study examines the challenges, barriers, and effectiveness of ICT-based instruction in education, focusing on word processing, basic computer hardware, web browsing, and educational games. The findings reveal that while teachers fully deliver lessons on fundamental ICT skills, students only partially acquire them, highlighting a gap in learning. The most frequently encountered challenges include slow internet connectivity, insufficient ICT training for teachers, and a lack of school resources, which hinder the effective integration of technology in classrooms. Despite these obstacles, educational games have demonstrated potential in engaging students, though their effectiveness depends on proper implementation and teacher preparedness. Previous research supports the need for improved ICT infrastructure and professional development programs to enhance digital literacy and learning outcomes. Addressing these challenges through targeted interventions can help bridge the gap between teaching and learning, ensuring that students maximize the benefits of ICT in education.